2017
DOI: 10.1016/j.molcel.2017.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin Linkage-Specific Affimers Reveal Insights into K6-Linked Ubiquitin Signaling

Abstract: SummarySeveral ubiquitin chain types have remained unstudied, mainly because tools and techniques to detect these posttranslational modifications are scarce. Linkage-specific antibodies have shaped our understanding of the roles and dynamics of polyubiquitin signals but are available for only five out of eight linkage types. We here characterize K6- and K33-linkage-specific “affimer” reagents as high-affinity ubiquitin interactors. Crystal structures of affimers bound to their cognate chain types reveal mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
149
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(159 citation statements)
references
References 64 publications
(109 reference statements)
10
149
0
Order By: Relevance
“…C) ubiquitination assays. In addition, by using a K6‐specific affimer, a linkage‐specific tool for the study of atypical K6 ubiquitin linkages, we found that the level of endogenous K6‐linked ASK1 polyubiquitination was almost undetectable under resting conditions in TRAF6‐deficient L02 hepatocytes, but was enhanced by TRAF6 reconstitution and increased much higher upon PA stimulation (Fig. D).…”
Section: Resultsmentioning
confidence: 91%
“…C) ubiquitination assays. In addition, by using a K6‐specific affimer, a linkage‐specific tool for the study of atypical K6 ubiquitin linkages, we found that the level of endogenous K6‐linked ASK1 polyubiquitination was almost undetectable under resting conditions in TRAF6‐deficient L02 hepatocytes, but was enhanced by TRAF6 reconstitution and increased much higher upon PA stimulation (Fig. D).…”
Section: Resultsmentioning
confidence: 91%
“…Abscisic acid‐insensitive 5‐like protein 1 (Wang, Li, Mao, Li, & Jing, ), ethylene‐responsive transcription factor RAP2‐12 (Kosmacz et al, ), auxin‐induced protein AUX28‐like (Xie et al, ), and auxin‐induced protein 22D‐like (Han et al, ) take part in plant growth and development regulated by plant hormones. E3 ubiquitin‐protein ligase CIP8‐like (Wang et al, ), E3 ubiquitin‐protein ligase RNF144B (Michel, Swatek, Hospenthal, & Komander, ), and ERAD‐associated E3 ubiquitin‐protein ligase HRD1B‐like are associated with ubiquitination (Wang, Ye, Lencer, & Hansen, ). Serine/threonine‐protein kinase (Dudek et al, ), 1‐phosphatidylinositol‐3‐phosphate 5‐kinase FAB1B (Hirano, Sato, & behavior, ), G‐type lectin S‐receptor‐like serine/threonine‐protein kinase (Sun et al, ), phosphatidylinositol 4‐phosphate 5‐kinase α (Honda et al, ), and so on are all genes in the selective sweep region that might allow plants to better adapt to the environment and have potential value for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that Tom1 recognizes oligoubiquitinated UFD substrates and either extends pre-formed chains or synthesizes new chains conjugated directly to the substrate, but using a residue distinct from K48 of the N-terminal ubiquitin moiety for chain attachment. Since HUWE1, the mammalian homologue, was shown to synthesize K6-and K11-linked chains (Michel et al, 2017;Yau et al, 2017), it is possible that Tom1 can use those lysine residues of the N-terminal ubiquitin moiety to initiate new chains. Moreover, detailed analysis of the banding pattern revealed that in the presence of Tom1 tri-ubiquitinated species of different apparent molecular weight were generated ( Fig 4E), indicating that ubiquitin conjugates synthesized by Tom1 and Ufd4 are clearly distinct.…”
Section: Tom1 Is An E4 Ligase Of the Ufdmentioning
confidence: 99%